Improved Supercapacitive Charge Storage in Electrospun Niobium Doped Titania Nanowires - Rajan, Jose; Baiju, Vidyadharan; Archana, P. S.; M. M., Yusoff; Jamil, Ismail (Royal Society of Chemistry, 2015)
Supercapacitors are emerging as a desirable energy storage medium in view of their order of magnitude higher power density than batteries and energy density than electronic capacitors. One of the key issues in the development of a suitable electrode material for supercapacitors is that materials showing large specific capacitance are poorly abundant. In this paper, we show that niobium doped titanium dioxide (Nb:TiO2) nanowires developed by electrospinning have an order of magnitude higher capacitance (~280 Fg-1) than pristine TiO2 (~40 Fg-1) or zirconium doped TiO2 (~30 Fg-1). The cyclic voltammetry and charge discharge cycling experiments show that the Nb:TiO2¬ nanowires have 100% coulombic efficiency and could be operated over 5000 cycles without any appreciable capacitance degradation. The superior charge storage capability of the Nb:TiO2 is assigned to its high electrical conductivity as determined by electrochemical impedance spectroscopy. A practical supercapacitor is fabricated in asymmetric configuration using the Nb:TiO2 as anode and activated carbon as cathode. The device delivered energy densities of 16.3, 11.4 and 5.6 Whkg-1 at power densities of 770, 1310, and 1900 Wkg-1, respectively. These values are much superior than a control device fabricated using activated carbon as its both electrodes.